The impact of implementing Imam al-Ghazali’s perception on self-monitoring (Muraqabah)on the development of healthy emotions among marine students during the pre-sea training - A. Shukor, Khairunnisa (Human Resource Management Academic Research Society, 2019)
Self-monitoring is considered as a crucial step in mastering self-regulation skill, which brings a person closer to achievement set up earlier. This study aims to investigate the implementation of self-monitoring in the light of Imam al-Ghazali’s perception, known as muraqabah and to explore the impact of implementing muraqabah on the development of healthy emotions. The number of 376 students were randomly selected from five public and private higher institutions that offering Marine-related courses. The students were all Muslims and have completed the pre-sea training. A set of questionnaire was developed from items selected through experts’ consensus of opinion (three-round modified Delphi method). The data collected were analysed descriptively (median and inter-quartile range) and inferentially (Spearman rhocorrelation analysis) using SPSS version 24. The study found that the level of muraqabah during the pre-sea training and the level of healthy emotions after completing the pre-sea training were both high (Med=4.00, JI==1.00). All items of muraqabah during the planning phase and the development of healthy emotions after the pre-sea training were positively and moderately correlated (rs(376)=.459, p<.001). The result shows that the implementation of muraqabah before the students implement the strategy to succeed the pre-sea training increases the development of healthy emotions after the students returned from the pre-sea training. It also shows that self-monitoring which enhances through religious valueshelps students to become emotionally healthy, thus, it develops healthy image about the world of seafaring.